b) \(3x+9=3x+6+3=3\left(x+2\right)+3⋮\left(x+2\right)\Leftrightarrow3⋮\left(x+2\right)\)
\(\Leftrightarrow x+2\inƯ\left(3\right)=\left\{-3,-1,1,3\right\}\Leftrightarrow x\in\left\{-5,-3,-1,1\right\}\).
a), c) tương tự.
d) \(\left(2x+1\right)⋮\left(3x-1\right)\Rightarrow3\left(2x+1\right)=6x+3=6x-2+5=2\left(3x-1\right)+5⋮\left(3x-1\right)\)
\(\Leftrightarrow5⋮\left(3x-1\right)\Leftrightarrow3x-1\inƯ\left(5\right)=\left\{-5,-1,1,5\right\}\Leftrightarrow x\in\left\{0,2\right\}\)(vì \(x\)nguyên)
Thử lại đều thỏa mãn.